2012
DOI: 10.7196/ajhpe.132
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy students' perception of their teachers' clinical teaching attributes

Abstract: Objective. Students' perspectives on clinical teaching attributes can contribute to knowledge on teaching and learning in clinical education. The objective of the study was to report on Nigerian physiotherapy students' perceptions of the clinical teaching skills of their teachers.Design and setting. A cross-sectional survey conducted in five physiotherapy training institutions in Nigeria.Subject. Physiotherapy students (N=203) in the clinical phase of their training participated in the study.Outcome measure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Students expected the relationship to be reciprocal, relaxed and open, so that they would feel comfortable asking questions. These findings resonate with findings in previous studies (Buccieri, Pivko & Olzenak 2013 ; Oyeyemi et al 2012 ). If these expectations were not addressed, the T-L relationship was affected negatively.…”
Section: Discussionsupporting
confidence: 93%
“…Students expected the relationship to be reciprocal, relaxed and open, so that they would feel comfortable asking questions. These findings resonate with findings in previous studies (Buccieri, Pivko & Olzenak 2013 ; Oyeyemi et al 2012 ). If these expectations were not addressed, the T-L relationship was affected negatively.…”
Section: Discussionsupporting
confidence: 93%
“…These characteristics were shared by 2 groups. Finally, findings of physicians' attitudes toward clinical learning showed that better education in the internship environment signals better learning, leading to better patient care (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…This insular training model typically based on hospitals existed during the early stage in the development of physiotherapy as a profession and no longer exists today. 5 The external model, now prevalent in the United States of America (USA), has theoretical education taught in an institution relatively divorced from clinical teaching provided in a clinical service setting of which students’ affiliation experiences take place in free-standing hospitals, clinics and centres. 5 The bridging model has separate institutions for theoretical and clinical education but with bridging arrangements to facilitate the clinical education.…”
Section: Introductionmentioning
confidence: 99%
“… 5 The external model, now prevalent in the United States of America (USA), has theoretical education taught in an institution relatively divorced from clinical teaching provided in a clinical service setting of which students’ affiliation experiences take place in free-standing hospitals, clinics and centres. 5 The bridging model has separate institutions for theoretical and clinical education but with bridging arrangements to facilitate the clinical education. The bridge version of clinical education organisation is in use in most Commonwealth countries, for which clinical rotations are organised in hospitals that are affiliated with respective universities.…”
Section: Introductionmentioning
confidence: 99%